G9a promotes muscular atrophy in chronic aging and acute denervation - Ying Jin; Wei Kang; Xiaoge Ji; Yihao Zhou; Ling Zheng (BMC, 2024)
Abstract Muscular atrophy accompanied by neuromuscular junction (NMJ) denervation is often observed after long-term chronic diseases and aging and is associated with substantial morbidity and mortality. Here, we report that histone methyltransferase G9a is elevated in the muscle of muscular atrophy model mice and that muscle-specific deficiency of G9a (Ehmt2 Ckmm−KO) alleviates muscular atrophy in both aged and denervated mice. Moreover, increased nerve-to-myofiber ratios and increased Agrin-Lrp4-MuSK signaling, which maintains NMJ, are found in aged Ehmt2 Ckmm−KO mice. Together, these data suggest that G9a promotes muscular atrophy and disrupts NMJ; thus, inhibiting the G9a level may be a potential therapy for muscular atrophy.